If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2r=-r+11
We move all terms to the left:
-2r-(-r+11)=0
We add all the numbers together, and all the variables
-2r-(-1r+11)=0
We get rid of parentheses
-2r+1r-11=0
We add all the numbers together, and all the variables
-1r-11=0
We move all terms containing r to the left, all other terms to the right
-r=11
r=11/-1
r=-11
| 6(y+3)+3=9 | | 10(x−1)=5(x+2) | | 8h-12=6h | | 3x+9=8x+14 | | t-10/4=-4 | | 17+w=19 | | t–104=-4 | | -5a+10a=10 | | -4=2(s+5) | | 1=-6z+5z | | 5(x+3)–3x=55 | | 69=-391+4x | | 18=7r+18 | | 2(y-6)+3=2y-7 | | 15x=69.6 | | 7n^2+10=-19n | | 18+7r=18 | | -2x+1=3x-4 | | 4x-3-3(2x)=12+3x | | (2x+15)+6=180 | | 50=-8z-2z | | 50=-8z–2z | | 3(u+3)=15 | | u/5+8=38 | | 9x-14=25 | | f(-4)=3(-4)-2 | | 7t+4=102−7t | | 5(z-2)+3z=1 | | 2x+2=x+ | | 10x+5=5x+60 | | y=-25(0)+170 | | 2f+7f+9=0 |